LEGAL PROTECTION FOR USERS OF ILLEGAL ONLINE LOAN SERVICES - Putri Rohmatul Hidayat (Universitas Muhammadiyah Gresik, 2022)
Online loan services or Peer to Peer Lending are one of the fintechs that are growing rapidly at this time. This growth is due to the ease and effectiveness of using fintech lending in providing loans to people who experience an increase in their living needs, especially since the COVID-19 pandemic. However, not all online loans have official permission from the Financial Services Authority, online loans that do not have official permission from the OJK or are called illegal online loans are very troubling to the public, recorded from 2019-2021 there were 19,711 complaints cases. Therefore, the authors conducted this study to provide public knowledge about the existence of legal protection for users of online loan services, especially users of illegal online loan services. This study uses a normative method by approaching the legislation. Legal protection for illegal online loan users is regulated in POJK No.77/POJK.01/2016 concerning Information Technology-Based Borrowing-Lending Services, where online loan service providers are required to apply the basic principles of user protection and OJK will provide administrative sanctions in the event of a violation.